2016
DOI: 10.1111/cdep.12187
|View full text |Cite
|
Sign up to set email alerts
|

Why Children Are Not Always Epistemically Vigilant: Cognitive Limits and Social Considerations

Abstract: Young children are thought to be motivated to avoid individuals who have been wrong in the past so as to minimize the risk of being misinformed. Yet they sometimes act on testimony from formerly inaccurate informants. Most explanations for this behavior have focused on limits in children's ability to process inaccurate testimony, such as difficulty inhibiting the normally appropriate bias to believe what people say. In this article, we argue that children may also use information from formerly inaccurate infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 47 publications
1
40
0
1
Order By: Relevance
“…Across studies, the results indicated that when two informants only differed in one characteristic, children asked and endorsed the informant who was more knowledgeable (in Meta‐analysis 1) or the informant with positive social characteristics (in Meta‐analysis 2). The effects revealed by these meta‐analyses were all medium to large, suggesting that although epistemic goals and social goals might rely on different mechanisms (see Brosseau‐Liard, ; Jaswal & Kondrad, ), they are both valuable to children when they evaluate the reliability of informants who differ on only one of these dimensions. The strength of these effects also supports that children have a relatively strong preference to acquire information from some informants over others.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Across studies, the results indicated that when two informants only differed in one characteristic, children asked and endorsed the informant who was more knowledgeable (in Meta‐analysis 1) or the informant with positive social characteristics (in Meta‐analysis 2). The effects revealed by these meta‐analyses were all medium to large, suggesting that although epistemic goals and social goals might rely on different mechanisms (see Brosseau‐Liard, ; Jaswal & Kondrad, ), they are both valuable to children when they evaluate the reliability of informants who differ on only one of these dimensions. The strength of these effects also supports that children have a relatively strong preference to acquire information from some informants over others.…”
Section: Discussionmentioning
confidence: 97%
“…These characteristics include age (VanderBorght & Jaswal, ), familiarity (e.g., Corriveau & Harris, ), language or national origin (Gaither et al, ; Kinzler, Corriveau, & Harris, ), and benevolent behavior (e.g., Johnston, Mills, & Landrum, ). Although social characteristics are not a direct indicator of an informant’s trustworthiness, trusting informants who share in‐group traits or who have positive social characteristics (e.g., accent, niceness) can be helpful for children to establish and maintain positive social relationships (Jaswal & Kondrad, ; Schillaci & Kelemen, ). In Meta‐analyses 1 and 2 of this study, we seek to estimate the effect sizes of children’s trust in an informant who is knowledgeable or an informant with positive social characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…In similar scenarios, 2‐ to 4‐year‐olds kept following the hints of an unreliable informant even when they conflicted with their own experience , when they had an incentive to ignore the testimony , and when the informant was introduced as a “big liar” . These findings have been interpreted as the manifestation of young children's bias to believe everything anyone claims or as the result of their pursuit of social rather than epistemic goals (such as affiliating with informants; ).…”
Section: What Are the Cognitive Foundations And Underpinnings Of Earlmentioning
confidence: 99%
“…Rather, they may recruit different social pragmatic forms of understanding shaped by children's own experiences in a given culture. Indeed, social factors (e.g., expressing respect, a desire to belong), and not just epistemic considerations, play a role in selective learning (Jaswal & Kondrad, 2016). Hence, just as prior social experiences are bound to affect children's dispositions to learn from others (Shneidman et al, 2016), this might also -and perhaps even more so -be the case for selective teaching.…”
Section: Discussionmentioning
confidence: 99%